THE INFLUENCE OF EMPLOYEE CREATIVITY ON EMPLOYEE PERFORMANCE WITH COMMITMENT AS A MODERATING VARIABLE - Erwanto, Erwanto; Yulia, Rasty; Andriani, Hertya; Herlinda, Herlinda; Rasyid, Abdul (ITB AAS Indonesia Surakarta, 2024)
This research is a quantitative study with an explanatory approach, namely an approach that relies on previous studies as the main formula for finding new variations/novelty in the research being conducted. The data used in this study are primary data obtained from 400 employees of Private Islamic Universities spread throughout Indonesia. The data were analyzed using the smart PLS 4.0 analysis tool. The result in this article show concluded that the Employee Creativity variable can have a positive relationship direction and a significant influence on Employee Performance because the P-Values point positively and are below the significance level of 0.05, namely 0.007. This is because the more creative employees can make work easily completed, problems can be overcome easily, and company targets can be achieved to improve Employee Performance. In line with the results of the first hypothesis, in the next row as a result of the second hypothesis also shows that the Commitment variable can strengthen the influence of the Work Creativity variable on Employee Performance because the P-Values are positive and below the significance level of 0.05, which is 0.000 more significant than direct testing of 0.007. Thus, the first and second hypotheses in this article can be accepted. Keywords: Employee Creativity, Employee Performance , Commitment